All Days 2013
DOI: 10.2118/163809-ms
|View full text |Cite
|
Sign up to set email alerts
|

ESP "Smart Flow" Integrates Quality and Control Data for Diagnostics and Optimization in Real Time

Abstract: Intelligent digital oilfield (iDOF) operations include the transfer, monitoring, visualization, analysis, and interpretation of real-time data. Enabling this process requires a significant investment to upgrade surface, subsurface, and well instrumentation and also the installation of a sophisticated infrastructure for data transmission and visualization. Once upgraded, the system then has the capability to transfer massive quantities of data, converting it into real information at the right time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The digital oilfield pilot implementation discussed in this paper is extensively documented in the literature (Al-Abbasi et al 2013;Al-Jasmi et al 2013a, 2013b, 2013c, 2013d, where various technical aspects are discussed; however, this is one of the few papers related to that particular project that discuss the change management aspects and, in particular, the effect that change has on people, or more succinctly, the people side change. Al-Abbasi et al (2013) note that "the ultimate purpose of collaborative IDOF workflows is to provide a more effective working environment for asset teams, allowing better communication and analysis to solve operational and management problems."…”
Section: Paper Discussionmentioning
confidence: 99%
“…The digital oilfield pilot implementation discussed in this paper is extensively documented in the literature (Al-Abbasi et al 2013;Al-Jasmi et al 2013a, 2013b, 2013c, 2013d, where various technical aspects are discussed; however, this is one of the few papers related to that particular project that discuss the change management aspects and, in particular, the effect that change has on people, or more succinctly, the people side change. Al-Abbasi et al (2013) note that "the ultimate purpose of collaborative IDOF workflows is to provide a more effective working environment for asset teams, allowing better communication and analysis to solve operational and management problems."…”
Section: Paper Discussionmentioning
confidence: 99%
“…The recommendation is to reduce the choke setting to increase the pressure intake (flowing bottomhole pressure (BHP)). Another interesting example is discussed in Al-Jasmi et al (2013a, 2013b. Each condition is associated with a set of verification as well as correcting actions; the former attempts to confirm what the degree of truth suggests, and the latter presents mostly corrective actions to help prevent the persistence of the conditions after the equipment has been replaced and ensures that measures are taken to help prevent the recurrence of the potential failure mechanism.…”
Section: Fig 7-esp Wells Advanced Diagnosticsmentioning
confidence: 99%
“…Recently, Al-Jasmi et al (2013a, 2013b showed the essential components of an automated workflow model that provides monitoring, diagnostic, and optimization in real time. In these publications, the authors describe the general aspect of FzL applied for predicting undesirable effects on ESP production.…”
Section: Introductionmentioning
confidence: 99%